2011
DOI: 10.1002/ajmg.c.30317
|View full text |Cite
|
Sign up to set email alerts
|

Cloacal exstrophy: An epidemiologic study from the International Clearinghouse for Birth Defects Surveillance and Research

Abstract: Cloacal exstrophy presents as a complex abdominal wall defect thought to result from a mesodermal abnormality. Anatomically, its main components are Omphalocele, bladder Exstrophy and Imperforate anus. Other associated malformations include renal malformations and Spine defects (OEIS complex). Historically, the prevalence ranges from 1 in 200,000 to 400,000 births, with higher rates in females. Cloacal exstrophy is likely etiologically heterogeneous as suggested by its recurrence in families and occurrence in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 61 publications
2
39
0
1
Order By: Relevance
“…The presented projects include (1) an effort to harmonise and standardise terminology in paediatric uroradiology, to avoid potentially misleading and unsafe perceptions and communications, (2) to update information on contrast-enhanced US in the paediatric genitourinary tract and (3) to try to assess whether all these efforts have an impact on daily imaging on a larger scale.…”
Section: Introductionmentioning
confidence: 99%
“…The presented projects include (1) an effort to harmonise and standardise terminology in paediatric uroradiology, to avoid potentially misleading and unsafe perceptions and communications, (2) to update information on contrast-enhanced US in the paediatric genitourinary tract and (3) to try to assess whether all these efforts have an impact on daily imaging on a larger scale.…”
Section: Introductionmentioning
confidence: 99%
“…Cloacal exstrophy has a varied incidence according to geographic location and is associated with several anomalies. Its incidence also increases when presented as a component of such conditions as imperforate anus, omphalocele, and spina bifida [4,7].…”
Section: Discussionmentioning
confidence: 94%
“…Through obstetric ultrasound, studies in animals have shown that these abdominal wall defects occur in the early stages of pregnancy and compromise the results of embryo formation and development [1,2,4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cloacal exstrophy is a rare but serious congenital abnormality that has an estimated prevalence of one case per 200,000-400,000 live births, with higher rates among females (36). Similar to bladder exstrophy, cloacal exstrophy involves a low AWD, absence of a visible bladder, and exstrophy of all the structures that form the cloaca (ie, rectum, bladder, and lower genitourinary tract).…”
Section: Cloacal Exstrophymentioning
confidence: 99%